Direct and indirect costs associated with ankylosing spondylitis and related disease activity scores in Turkey - DİRESKENELİ, RAFİ HANER (SPRINGER HEIDELBERG, 2015)
This study assessed quality of life, direct and indirect healthcare costs related to ankylosing spondylitis (AS). This study included 650 prevalent AS patients visiting seven centers at tertiary healthcare institutions in Turkey who were interviewed using a standard questionnaire to determine annual direct and indirect healthcare costs. Eligible patients were age a parts per thousand yen18 years with AS for at least 12 months. Direct costs were categorized as inpatient, outpatient and pharmacy, and AS-related consultation. Indirect costs were categorized as workday loss, additional AS-related costs, and caregiver costs. Clinical outcome measures were obtained, including Patients' Global Disease Activity (Pt-GDA); visual analog scale (Pain-VAS) for pain; Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Functional Index (BASFI), and Metrology Index (BASMI) scores, and EuroQoL 5 dimension (EQ-5D) health status survey scores. Mean (a,not sign4,335.20) and median (a,not sign5,671.00) annual costs per patient were calculated. Pharmacy costs (a,not sign4,032.73) were highest among overall expenditures, followed by additional AS-related consultation (a,not sign2,480.38), outpatient (a,not sign225.02), and inpatient costs (a,not sign29.98). Over half of AS patients (54.8 %) experienced work loss. Related average annual costs were a,not sign414.16, based on income level. 10.3 % of AS patients incurred an additional a,not sign2,008.07 in 1 year. 6.8 % of patients required caregivers and incurred a,not sign778.70 in average annual patient paid costs. Mean Pt-GDA, Pain-VAS, EQ-5D, BASDAI, BASFI, and BASMI scores were 4.4, 40.5, 62.7, 3.6, 3.1, and 2.9, respectively. Direct and indirect AS-related costs are high and represent a considerable economic burden on Turkish AS patients.
Keywords: Ankylosing spondylitis; Direct costs; Indirect costs; Turkey; 3 EUROPEAN COUNTRIES; QUALITY-OF-LIFE; RHEUMATOID-ARTHRITIS; BATH; RELIABILITY; PREVALENCE; VALIDITY; INDEX; ONSET; CARE